2020
DOI: 10.1371/journal.pone.0228259
|View full text |Cite
|
Sign up to set email alerts
|

Exploring demands of hemodialysis patients in Taiwan: A two-step cluster analysis

Abstract: Aims and objectivesTo classify hemodialysis patients into subgroups via cluster analysis according to the Somatic Symptoms Disturbance Index, Taiwanese Depression Scale, and Herth Hope Index scores. Patient demands in each cluster were also examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A study from Malaysia found that dialysis patients having religion was associated with lower depression scores [44]. A positive correlation between hope and religious beliefs was found in patients undergoing haemodialysis; in that study, 97% of patients attributed their hope to religious beliefs [45 ▪ ].…”
Section: Related Risk Factorsmentioning
confidence: 80%
“…A study from Malaysia found that dialysis patients having religion was associated with lower depression scores [44]. A positive correlation between hope and religious beliefs was found in patients undergoing haemodialysis; in that study, 97% of patients attributed their hope to religious beliefs [45 ▪ ].…”
Section: Related Risk Factorsmentioning
confidence: 80%
“…This finding may be due to Taiwan having a National Health Insurance scheme that subsidizes patients with major illnesses, injuries, and disabilities. These measures affect patients’ financial status and dialysis compliance, which are associated with healthcare insurance and social welfare, as suggested by previous studies [ 74 , 75 , 76 , 77 , 78 ]. In addition, Taiwanese HD patients’ five-year cumulative survival was 54.2% from 2009 to 2013, higher than that of American patients in 2012 (41.4%) and Canadian patients in 2011 (41.8%; 2020 Taiwan Society of Nephrology Annual Report).…”
Section: Discussionmentioning
confidence: 92%
“…RRTs include kidney transplantation and dialysis, of which hemodialysis (HD) is the most common form of intervention in most countries. In 2015 alone, 83,808 patients in Taiwan received dialysis treatment [ 1 ]. However, patients on dialysis have an increased risk of malignancy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%